2008
DOI: 10.1111/j.1439-0272.2008.00858.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of E-SOD, GPX5 mRNAs and immunoexpression of Cu/ZnSOD in epididymal epithelial cells of finasteride-treated rats

Abstract: We studied the immunoexpression of Cu/Zn superoxide dismutase (Cu/ZnSOD) and mRNAs expression of extracellular superoxide dismutase (E-SOD), and epididymal specific glutathione peroxidase 5 (GPX5), in epithelial cells of caput and cauda epididymis of rats treated with finasteride, a steroid-based inhibitor of 5alpha-reductase. The 5alpha-reductase is known to exist in two isoforms. Both 5alpha-red1 and 5alpha-red2 catalyse the irreversible conversion of T into DHT. Formation of DHT in the epididymis is mostly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
0
8
0
4
Order By: Relevance
“…Therefore, in our study (carried out with mature rats), we inhibited the 5a-red2 activity by finasteride, which is used in basic and clinical studies as the one of the best inhibitors of the enzyme [23,30]. In our previous studies, we had found that 28 and 56 day DHT-deficiency altered the androgen receptor (AR) [31], estrogen a and b receptors (ERa, ERb) in epididymis [32], antioxidant enzymes (GPX5, E-SOD, Cu/Zn SOD) [33] and inducible nitric oxide synthase (iNOS) [34] expression patterns. The changes in the morphology of testes were noticed after a long period (56 days) of androgen imbalance [35].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in our study (carried out with mature rats), we inhibited the 5a-red2 activity by finasteride, which is used in basic and clinical studies as the one of the best inhibitors of the enzyme [23,30]. In our previous studies, we had found that 28 and 56 day DHT-deficiency altered the androgen receptor (AR) [31], estrogen a and b receptors (ERa, ERb) in epididymis [32], antioxidant enzymes (GPX5, E-SOD, Cu/Zn SOD) [33] and inducible nitric oxide synthase (iNOS) [34] expression patterns. The changes in the morphology of testes were noticed after a long period (56 days) of androgen imbalance [35].…”
Section: Introductionmentioning
confidence: 99%
“…In general, other male reproductive toxins such as chlorpyrifos (insecticide) [87], atrazine (pesticide) [60], and nonylphenol (ED) [56], that postnatally influence an organism also caused a reduction in plasma testosterone concentration. Similarly, the inhibition of 5α-reductase 2 activity by finasteride changed plasma androgen concentrations in finasteride-treated adult male rats [37] and in male offspring of these rats [38]. The differences in androgen levels between the F1:Fin and F1:Control groups of rats exhibit some resemblance to the results of studies which explored prenatal exposure to anti-androgenic endocrine disruptors such as flutamide [88] or vinclozolin [89] that reduced serum testosterone concentrations in adult animals.…”
Section: Endocrine Disruptors and Changes In Epididymal Antioxidant Ementioning
confidence: 66%
“…Methoxychlor similarly decreased the activity of antioxidant enzymes (SOD, CAT, GR, GPX) in the epididymis with respect to the regions of the organ [59]. The study by Kolasa et al [37] demonstrated that finasteride treatment of adult rats changed the epididymal region-specific immunoexpression of antioxidant enzymes (GPX5: increase in the caput of treated rats compared to control rats; E-SOD: increase in the caput and decrease in the cauda of treated rats). Also, treatment of Wistar male rats with ethanol and atrazine showed diverse results: CAT activity in epididymal homogenates decreased, SOD and GPX activity increased [60].…”
Section: Endocrine Disruptors and Changes In Epididymal Antioxidant Ementioning
confidence: 92%
See 2 more Smart Citations